Pengaruh Pengendalian Internal Dan Moralitas Individu Terhadap Risiko Kecurangan Orderan (Studi Kasus Go-Jek Di Gorontalo) - Pongoliu, Yayu Isyana D; Duhu, Siti Sahrina S La; Thaib, Diva Nadya; Mustapa, Siti Yuliyani (Peneliti.net, 2024)
The purpose of this study is to determine how morality and personal internal control impact the fraudulent of order cheating in Go-Jek transportation firms. This research is important to study because it can provide insight into how internal control and individual morality affect the risk of Go-Jek order fraud in Gorontalo. The data in this study were analyzed using multiple linear regression method. The samples used 100 Go-Jek drivers in Gorontalo, the research findings demonstrate that internal control and individual morality have a negative and significant impact on the risk of order cheating on Go-Jek online transport services. So that increasing the effectiveness of internal control and strengthening the value of individual morality in drivers has the potential to reduce the risk of order fraud.